Convex semigroups on Banach lattices - Robert Denk; Michael Kupper; Max Nendel (Bielefeld University, Center for Mathematical Economics (IMW), 2019)
In this paper, we investigate convex semigroups on Banach lattices. First, we consider the case, where the Banach lattice is σ-Dedekind complete and satisfies a monotone convergence property, having Lp-spaces in mind as a typical application. Second, we consider monotone convex semigroups on a Banach lattice, which is a Riesz subspace of a σ-Dedekind complete Banach lattice, where we consider the space of bounded uniformly continuous functions as a typical example. In both cases, we prove the invariance of a suitable domain for the generator under the semigroup. As a consequence, we obtain the uniqueness of the semigroup in terms of the generator. The results are discussed in several examples such as semilinear heat equations (g-expectation), nonlinear integro-differential equations (uncertain compound Poisson processes), fully nonlinear partial differential equations (uncertain shift semigroup and G-expectation).
urn:nbn:de:0070-pub-29372580
Keywords: 330; Convex semigroup; nonlinear Cauchy problem; fully nonlinear PDE; well-posedness and uniqueness; Hamilton-Jacobi-Bellman equations